Pengembangan Media Permainan Monopoli Berbasis STAD (Student Teams Achievement Division) Pada Pelajaran PKN Materi Pancasila Di Kelas VI MI R. Khufadz - Sulis Handayani (Al-Riwayah : Jurnal Kependidikan, 2025)
The objective of this research is to develop STAD-based monopoly game media for Pancasila material in Civics Education learning at MI R. Khufadz for grade VI students. Research and Development (R&D) is the type of research employed using the ADDIE development model. This study involved 17 sixth-grade students at MI R. Khufadz in Sorong Regency. Questionnaires, documentation, observation, as well as pre-test and post-test were the data collection methods. The research results indicate that the material expert validation sheet obtained a score of 40% (categorized as "less valid") and the media expert validation sheet obtained a score of 68% (categorized as "valid"). With an average validity score of 54%, the monopoly game media falls into the "moderately valid" category and requires improvement before implementation. The student response questionnaire results obtained a score of 87.37% and the teacher response questionnaire obtained a score of 92.30%, with an average practicality of 89.83%. Pre-test and post-test data showed an improvement in students' understanding of Pancasila material by 23.5% after using the STAD-based monopoly media. Therefore, it can be concluded that the developed monopoly game falls into the "very practical" category but requires material improvements before full implementation.